Revalorando la oralidad en las cumananas de Tumbes - Marchán Aylas, Carol Lissett (2025)
The study presents a sample of the analysis of the cumananas of Tumbes with the purpose of exposing its structure, its thematic fields and the lexicon used.Furthermore, it is intended to show that, although the cumanana presents variations in its form of manifestation, it continues to be cultivated and revalued in Tumbes, and it is the reflection of a culture that, through orality and writing, endures through time.